Система коммутации с распределенным управлением - Сигарев, А.А.; Душеба, В.В. (Моделювання та інформаційні технології, 2009)
The article is devoted the decision of problem of removal of such failings as: conflicts of access; difficulty of realization of more effective asynchronous mode of interprocessor exchange, which are caused application of the centralized management in the methods of switching of informative channels.